PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SEKOLAH DASAR MUHAMMADIYAH 002 ALAM PANJANG - Muhammad Yuzar; Otang Kurniaman; Gustimal Witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by the fact that the learning outcomes of students in science subjects has not been optimal. Based on initial observations that researchers do dikatahui that only 50% or 10 of the total 20 students who received grades above KKM, while 50% or 10 out of 20 students expressed an incomplete or gain value is still below the KKM. This research is a classroom action research conducted in Class IV SD Muhammadiyah 002 Alam Panjang. Research instruments consisted of a Learning Tool used in this research is guided by the Education Unit Level Curriculum (SBC), known as Curriculum 2006 learning device consists of a syllabus, lesson plans, student worksheets and observation sheet. The first meeting of the cycle to the first activity that teachers are only 50% to the category of "pretty perfect" at the meeting to 2 with the percentage of 59% in the category "simply perfect". At a meeting of all three activities that teachers do 70% to the category of "perfect" while in attendance to 4 activities that teachers do 79% also in the category of "perfect". Based on data analysis of student activity first meeting sikuls I average student activity 54% with the classification of "High Enough" at the second meeting of the average activity increased to 62% with the classification of "High Enough" At the third meeting of the second cycle the average student activity 75 % on the classification of "High" and the fourth meeting increased compared with the previous meetings by an average of 83% of student activity with the classification of "Very High". The first cycle, it is known that the number of students who reached the KKM is 15 students (75%) of 20 students. That is an increase of student learning outcomes IPA base score. Cycle II, the number of students who reached the KKM amounted to 17 (85%) of 20 students, improving student learning outcomes in the first cycle reached (33%) and in cycle II to be increased to reach (41%) Keywords: cooperative learning model make a match, the result of learning science